2015
DOI: 10.2147/ijn.s77731
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan based atorvastatin nanocrystals: effect of cationic charge on particle size, formulation stability, and in-vivo efficacy

Abstract: Cationic charged chitosan as stabilizer was evaluated in preparation of nanocrystals using probe sonication method. The influence of cationic charge densities of chitosan (low CS L , medium CS M , high CS H molecular weights) and Labrasol ® in solubility enhancement and modifying the release was investigated, using atorvastatin (ATR) as poorly soluble model drug. Compared to CS M and CS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…Recently a research group have reported the use of chitosan as a cationic stabilizer for preparation of itraconazole nanocrystals using the conventional method of HPH method and investigated its stabilization effect. Physical stability of prepared nanocrystals was found to be significantly improved without any changes or new modification observed in crystal structure 94 . Another research group working on chitosan-based atorvastatin nanocrystals investigated the effect of the cationic charge of stabilizer on the nanocrystals particle size and stability.…”
Section: Parenteral Nanosuspensionmentioning
confidence: 93%
See 1 more Smart Citation
“…Recently a research group have reported the use of chitosan as a cationic stabilizer for preparation of itraconazole nanocrystals using the conventional method of HPH method and investigated its stabilization effect. Physical stability of prepared nanocrystals was found to be significantly improved without any changes or new modification observed in crystal structure 94 . Another research group working on chitosan-based atorvastatin nanocrystals investigated the effect of the cationic charge of stabilizer on the nanocrystals particle size and stability.…”
Section: Parenteral Nanosuspensionmentioning
confidence: 93%
“…Another research group working on chitosan-based atorvastatin nanocrystals investigated the effect of the cationic charge of stabilizer on the nanocrystals particle size and stability. Nanocrystals of the drug were prepared with desired specifications and effect of chitosan as potential stabilizer has been evaluated 94 .…”
Section: Parenteral Nanosuspensionmentioning
confidence: 99%
“…When their concentrations are very low, formed nanoparticles show larger particle sizes and even higher concentrations of these factors, resulting in the formation of larger nanoparticles. This might be because of the repulsion of amino groups in chitosan molecules at higher concentrations and the addition of poloxamer 188 might promote further aggregation, which leads to precipitation, forming NPs with larger particle sizes [31]. The size of NPs can affect their distribution, for which lower liver uptake can be observed with smaller particle sizes of 25-50 nm in comparison to 150-300 nm-sized NPs and thus bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…Nanocrystals are having the atoms size in the range of 10-400 nm, prepared from nanosuspension consisting of the following steps. i) preparation of nanosuspension, ii) wet milling, iii) high pressure homogenization iv) nanocrystallization and v) spray drying [24,25] . Mallesh Kurakula et al, have investigated the efficacy of nanocrystals in enhancing the solubility and dissolution rate of Atorvastatin [26] .…”
Section: Novel Technologies In Delivery Of Poorly Soluble Drugsmentioning
confidence: 99%